Clinical Value and Prognosis of C Reactive Protein to Lymphocyte Ratio in Severe Aneurysmal Subarachnoid Hemorrhage - Zhang, Qingqing; Zhang, Gaoqi; Wang, Lintao; Zhang, Wanwan; Hou, Fandi; Zheng, Zhanqiang; Guo, Yong; Chen, Zhongcan; Hernesniemi, Juha; Andrade-Barazarte, Hugo; Feng, Guang; Gu, Jianjun (Frontiers in Neurology, 2022)
Objective:To investigate the relationship between CLR and disease severity and clinical prognosis of aSAH. Methods:The authors retrospectively analyzed the clinical data of 221 aSAH patients who were admitted to intensive care unit from January 2017 to December 2020. The indicators of inflammatory factors in the first blood routine examination within 48 hours of bleeding were obtained. The prognosis was evaluated by mRS score at discharge, mRS>2 was poor outcome. Through the ROC curve, the area under the curve was calculated and the predicted values of inflammatory factors (CLR, CRP, WBC, neutrophils) were compared. Univariate and multivariable logistic regression analyses were used to evaluate the relationship between CLR and the clinical prognosis of patients. ROC curve analysis was performed to determine the optimal cut-off threshold, sensitivity and specificity of CLR in predicting prognosis at admission. Results:According to the mRS score at discharge, 139 (62.90%) patients were classified as poor outcome (mRS>2). The inflammatory factor with the best predictive value was CLR, which had an optimal cut-off threshold of 10.81 and an area under the ROC curve of 0.840 (95%CI 0.788-0.892,P<0.001). Multivariable Logistic regression analysis showed that the Modified Fisher grade, Hunt-Hess grade and CLR at admission were independent risk factors for poor outcome of patients with aSAH (P<0.05). According to Hunt-Hess grade, patients were divided into mild group (Hunt-Hess≤3) and severe group (Hunt-Hess>3), and CLR value was significantly higher in severe aSAH patients than in mild patients. The optimal cut-off threshold of CLR in the severe group was 6.87, and the area under ROC curve was 0.838 (95% CI 0.752-0.925,P<0.001). Conclusions:The CLR value at admission of patients with aSAH was significantly associated with Hunt-Hess grade, The higher Hunt-Hess grade, the higher the CLR value,and the worse the prognosis. Early CLR value can be considered as a feasible biomarker to predict the clinical prognosis of aSAH patients.